Sex-Specific Differences in Essential Lipid Requirements of Daphnia magna - Martin-Creuzburg, Dominik; Massier, Tamara; Wacker, Alexander (Frontiers in Ecology and Evolution, 2018)
Sex-specific differences in nutritional requirements may crucially influence the performances of the sexes, which may have implications for sexual reproduction and thus is of great ecological and evolutionary interest. In the freshwater model species Daphnia magna, essential lipid requirements have been extensively studied. Dietary deficiencies in sterols and polyunsaturated fatty acids (PUFA) have been shown to constrain somatic growth and parthenogenetic reproduction of female Daphnia. In contrast, nutrient requirements of male Daphnia have not been studied yet. Supplementation experiments were conducted to investigate differences in sterol (cholesterol) and PUFA (eicosapentaenoic acid, EPA) requirements between female and male D. magna. Thresholds for sterol-limited juvenile growth were higher in females than in males, suggesting that females are more susceptible to dietary sterol deficiencies than males. Sex-specific differences in maximum somatic growth rates were evident primarily in the presence of dietary EPA; females could not exploit their generally higher growth potential in the absence of dietary PUFA. However, the thresholds for EPA-limited growth did not differ between sexes, suggesting that both sexes have similar dietary EPA requirements during juvenile growth. During a life history experiment, the gain in body dry mass was higher in females than in males, irrespective of food treatment. In both sexes, the gain in body dry mass increased significantly upon EPA supplementation, indicating that both sexes benefited from dietary EPA supply also later in life. However, the positive effects of EPA supplementation were most pronounced for female reproduction-related traits (i.e. clutch sizes, egg dry masses, and total dry mass investment in reproduction). The high maternal investment in reproduction resulted in a depletion of nutrients in female somata. In contrast, the comparatively low paternal investment in reproduction allowed for the accumulation of nutrients in male somata. We conclude that males are generally less susceptible to dietary nutrient deficiencies than females, because they can rely more on internal body stores. Our data suggest that the performances of the sexes are differentially influenced by lipid-mediated food quality, which may have consequences for sexual reproduction and thus the production of resting eggs and the maintenance of Daphnia populations.